Development Of Education In Post Tsunami Aceh - Mujiburrahman, Mujiburrahman (Jurnal Kompetensi, 2012)
Discussing about the development of education in Aceh is not far from the aspect of Aceh’s long history. The development of education in Aceh has run in some phases. Education is very broad but this paper focuses only on aspects of education development in Aceh post-tsunami. Discussions on the development of education in post-tsunami Aceh focus on two aspects, namely formal and informal education. Earthquake and tsunami hit Aceh on December 26, 2004 had extremely changed many aspects of life, including education aspects. The data from the Department of Education reports that 25,000 students and 2,248 teachers died and 2153 school buildings were destroyed or heavily damaged. As a result, Aceh education sectors were in severe condition. It is not exaggerated to say that education in Aceh was coming into "dark ages." After the earthquake and tsunami tragedy, a new Aceh history of education has emerged. Various aids given by countries and international, national, and local NGOs, both formal and informal education has been given opportunities to develop. Education development aimed at two aspects i.e. development of infrastructure and human resources. Changes in both aspects of development have resulted in better education atmospheres in Aceh.